Analysis of Raw Material Control Using Economic Order Quantity (EOQ) Method In Suppressing Inventory Costs At UD. Sagga Lather Malang.: Yustus S. Boky, Ali Hanafiah - yustus S Boby (STIA MALANG, 2019)
Abstract This study aims to determine the quantity or quantity of economic orders (EOQ), safety stock, point of re-ordering, and the total cost of raw materials inventory of skin on UD. Sagga Leather. The data used in this study consist of primary data and secondary data both qualitative and quantitative in relation to the stock of paper raw materials. Primary data obtained through observation as well as direct interviews with various parties concerned. Secondary data is obtained from company management documents and reports. The results of this study indicate that the application of EOQ (Economic Order Quantity) method on UD. Sagga Leather Malang is more efficient than the simple method used by the company. The application of this method does emphasize how important the raw material inventory planning for the company in the production process. Keywords: Economical order quantity (EOQ), Inventory.